2016
DOI: 10.3109/15368378.2016.1144063
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiation (2.45 GHz)-induced oxidative stress: Whole-body exposure effect on histopathology of Wistar rats

Abstract: Man-made microwave and radiofrequency (RF) radiation technologies have been steadily increasing with the growing demand of electronic appliances such as microwave oven and cell phones. These appliances affect biological systems by increasing free radicals, thus leading to oxidative damage. The aim of this study was to explore the effect of 2.45 GHz microwave radiation on histology and the level of lipid peroxide (LPO) in Wistar rats. Sixty-day-old male Wistar rats with 180 ± 10 g body weight were used for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
(53 reference statements)
3
39
0
1
Order By: Relevance
“…Several studies have demonstrated the negative impact of MW radiation exposure on male reproductive health which may affect male fertility . Reports are there mentioning the ill effects of short duration exposure to MW radiation on gonadotropin levels (FSH and LH), testicular morphology, histopathology, serum/plasma testosterone levels, sperm counts, and sperm viability . Studies demonstrate that short term exposure to 2.45 GHz MW radiation may lead to testicular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the negative impact of MW radiation exposure on male reproductive health which may affect male fertility . Reports are there mentioning the ill effects of short duration exposure to MW radiation on gonadotropin levels (FSH and LH), testicular morphology, histopathology, serum/plasma testosterone levels, sperm counts, and sperm viability . Studies demonstrate that short term exposure to 2.45 GHz MW radiation may lead to testicular apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chauhan et al [30] stated significant increase in lipid peroxidation after microwave exposure. This was explained that microwave radiation is suggested to have the potential of changing the biological lipid membranes and the outcomes of these changes can be seen in the structural and functional properties of a cell.…”
Section: Discussionmentioning
confidence: 99%
“…This is exactly in line with previous studies (Chen et al, 2014; Lee et al, 2005; Maaroufi et al, 2014). In addition, EMF exposure also induce oxidative stress of the brain, liver, kidney, and of testis tissues (Chauhan et al, 2017). As indicated above, some previous research failed to find negative effects resulting from EMF exposure, and even reported that EMF exposure had positive effects on spatial learning and memory (Abedi et al, 2011; Banaceur et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%